Optimization of sowing time to mitigate heat stress in spring maize (Zea mays) in Indo-Gangetic plains of India - Bamboriya, Shanti Devi; Sepat, Seema; Kumar, Ramesh; Jat, Shankar Lal; Rakshit, Sujay; Zaidi, Pervez H. (Indian Council of Agricultural Research, 2025)
In spring maize (Zea mays L.) prone to heat stress, especially at terminal stages, understanding the impact of sowing time on important genotypes for heat stress tolerance is crucial to optimize yield. An experiment was conducted during 2020 and 2021 at the Research farm of ICAR-Indian Institute of Maize Research, Ludhiana, Punjab to study the effect of sowing time and genotype interactions on yield and heat stress in spring maize. The experiment was laid out in a split-plot design (SPD) comprised of 4 different sowing dates, viz. 15th February; 25th February; 5th March; and 15th March, and 4 maize genotypes, viz. PMH1; PMH10; CoH(M)6; and CoH(M)8, replicated thrice. Spring maize sown on 15th February gave a higher grain yield (8.5 t/ha). Successive delays of 10, 20, and 30 days in sowing of spring maize caused significant yield penalties of 15%, 24%, and 29%, respectively. Heat stress at flowering was observed with delayed sowing (5th and 15th March), leading to a ~20% yield decline compared to non-stressed conditions (15th February). Furthermore, sowing beyond 15 February resulted in a shortening of vegetative (4–15 days) and reproductive (3–8 days) periods. Spring maize sown on 15 February gave higher water productivity (16–34%) compared to delayed sowings. Among genotypes, PMH 1 recorded a higher yield (8.2 t/ha) under non-stressed conditions with early sowing on 15th February. However, under heat stress, PMH 10 gave a higher yield (6.5 t/ha) sown on 25th February. Overall, it could be concluded that spring maize sowing up to 15th February is the optimum time to avoid heat stress at the flowering stage to achieve higher yield in north-western regions of India.